The Notion of Divine Principle (Asas Ilahiah) in Indonesian Contract Law - Djumikasih, Djumikasih; Luth, Thohir; Budiono, Abdul Rachmad; Koeswahyono, Imam (Faculty of Law, Universitas Brawijaya, 2021)
This study is legal research aiming to find out the essence of Divine Principles in Indonesian Contract Law from the review of the Natural Law theory, the Sunt-Servanda theory, the Awareness and Legal Obedience Grundnorm theory, and Truth theory. This research reveals that the Divine Principle's essence is the most fundamental principle or guideline derived from God but exists in humans, aiming to find the truth and regulate the parties in making agreements. The application of the Divine Principle aims to find the truth and regulate the parties in the agreement's field. Indonesian citizens could realize and practice the Precepts of Godhead in their agreement activities. In establishing the agreement, the parties are applying the teachings of their respective religions. This study reveals that the Divine principle needs to be incorporated into one of the upcoming National Agreement Laws principles, especially in the contract born because of the agreement. This study maintains that the divine principle can be applied comprehensively for Indonesian citizens who are parties to the agreement, not only limited to the Indonesian Muslim citizens.